Subjectivity Bias Elimination in Employee Appraisal Process – Role of People Analytics - Saha , Debadrito (Gyan Management Journal, 2022)
Purpose: This research serves the purpose of dealing with different types of Human Subjective Biases in Performance Management System by interview-based analysis and content analysis depending upon inputs from renowned HR professionals and then to determine if HR Analytics can help the HR practitioners in objective-decision making rather than intuition in PMS.Design/Methodology/Approach: Focused-Group-Interview approach is followed here to acquire in-depth information about Subjectivity Bias Elimination in Employee Appraisal Process and how the same can be mitigated with the help of People Analytics. Findings: This research will reveal the truth of erroneous subjective judgments based on instincts and how HR Analytics can help the HR practitioners in objective decision making rather than intuition in PMS. Originality/ Value: This research identifies factors leading to Subjectivity Bias in Employee Appraisal Process. It suggests updated criteria for HR professionals to mitigate subjectivity bias in Employee Appraisal Process with help of People Analytics.